2019
DOI: 10.2528/pierm19032511
|View full text |Cite
|
Sign up to set email alerts
|

Subspace Clutter Removal Techniques in GPR Images

Abstract: In many modern GPR systems, it is desired to detect the presence of targets in the interference which includes clutter and noise. Detection of water leaks using GPR has been aimed in this work. Pipe and soil are known as the clutter of data in this scenario. Various signal processing techniques like multivariate subspace-based algorithms are proposed to effectively suppress the clutter and increase the signal to interference ratio. Combining Independent Component Analysis (ICA) and Principal Component Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Germane cognitive load refers to instructional manipulations that assist the learner to use working memory resources to learn a specific activity or task. Shehab (2011) confirmed that long-term memory is the main knowledge storage for new knowledge and skills, whereas working memory underlies the processing of new information. Grobe (2018) stated that information store principle is a huge long-term memory capacity to store organized information in the form of schemas that can be handled as a single element in working memory.…”
Section: Sweller Et Almentioning
confidence: 68%
“…Germane cognitive load refers to instructional manipulations that assist the learner to use working memory resources to learn a specific activity or task. Shehab (2011) confirmed that long-term memory is the main knowledge storage for new knowledge and skills, whereas working memory underlies the processing of new information. Grobe (2018) stated that information store principle is a huge long-term memory capacity to store organized information in the form of schemas that can be handled as a single element in working memory.…”
Section: Sweller Et Almentioning
confidence: 68%
“…Two of the benchmark cases include different data sets generated using PCA 26 , 47 , 48 . The first one consists of features extracted using PCA similar as in study 26 for the purpose of dimensionality reduction of the B-scan.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the input vector is prepared to have the size of 1 × 874 for the proposed M2LP framework. The second benchmark case is specialized on clutter reduction by using PCA 47 , 48 , where only the reflections coming from the buried object are obtained and linear regression technique is employed to identify hyperbolic signatures of the B-scan data. After that, the proposed deep-learning-based approach, M2LP framework is used to carry out buried object characterization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent eigenvalues result from environmental clutter and only a minor part is due to system noise. When only two subspaces are used (noise and data), the clutter is part of the data matrix and cannot be removed (Sabushimike et al, 2016;Shehab et al, 2019). Considering additive noise, a measured frame of a radar system A meas is an M × N matrix, where N is the number of chirps and M is the number of time-steps.…”
Section: Data and Noise Subspacesmentioning
confidence: 99%